Arduino Embedded Control System of DC Motor Using Proportional Integral Derivative - Iswanto, Alfian Ma’arif, Riky Dwi Puriyanto, Nia Maharani Raharja, Safinta Nurindra Rahmadhia (International Journal of Control and Automation, 2020)
DC Motor has a lot of applications in the control system, robotics, industrial, and power system. The easiest and most popular control method to control DC motor is Proportional-Integral-Derivative (PID) Control. The proposed simulation has done with the great performance of the augmented system. However, simulation is an ideal situation, and most-likely is different from real-time hardware implementation. Hence, the research proposes hardware design and implementation of controlling the angular speed of the DC motor in Arduino Uno as its embedded processor system, using a PID Controller. Some examinations and analysis are done in the research, such as open-loop test, step-response, and the effect of PID parameters and sample time to the system performance. The PID controller is successfully implemented to Arduino UNO and able to control the angular speed of the DC motor. System performances differ according to the choice of PID parameters and sample time. The best PID parameters are Kp=0.7, Ki=0.3, and Kd=0.2 in 50ms sample time, as system response has no overshoot, no undershoot, fast rise, and settling time.